Analysis of quality of life in patients with Lyme disease - Delikatna, Tetyana; Malyi, Vasyl (Annals of Mechnikov's Institute, 2021)
Introduction. Lyme disease is a multisystem infectious disease with a high risk of chronization which leads to disability and reduced QOL of patients. The study of QOL is a relatively new area of clinical research. One of the most common general questionnaires is the Short Form Medical Outcomes Study (SF-36). The aim of the study was to investigate the level of QOL in patients with LD in comparison with almost healthy individuals and to establish the gender characteristics of different components of health. Material & methods. The main group included 45 patients with LD of moderate severity in the stage of local infection, erythema migrans. The mean age of patients was (45.89 ± 2.06) years, of whom 22 (48.88%) were men and 23 (51.12%) were women. Patients were hospitalized for an average of (25 ± 3.96) days from the onset of the disease. The diagnosis was verified on the basis of an epidemiological anamnesis (tick bite), clinic (erythema migrans), serological tests (detection of antibodies to B. burgdorferi). Patients were divided by gender into 2 subgroups. The mean age was the same and was in men (42.06 ± 2.78) years, in women – (49.53 ± 3.01) years. Assessment of QOL of patients and comparison groups was performed on eight scales: 1 - physical functioning, 2 - role functioning due to physical condition, 3 - pain intensity s activity, 4 - general health, 5 - vital activity, 6 - social functioning, 7 - role functioning due to emotional state, 8 - mental health. Used clinical methods, questionnaires, mathematical processing. All data were entered into the "Electronic Study Card". The results of clinical examinations and studies were processed by the method of variation statistics (Student's t-test) using computer programs Microsoft Office Excel 2010, Statistica 10 and online calculator. Results & discussion. Surveys of practically healthy people and patients with Lyme disease were conducted, the features of physical and mental components of health depending on gender were studied. In terms of gender, physical and emotional health are better in men than in women. Practically healthy men are the most satisfactory in the field of physical and mental functioning, and women with Lyme disease are the least satisfied. Mental health indicators on the scale of vital activity and social functioning in patients at the average level indicate that the disease does not affect the social life of patients. The lowest indicators on the scales of role functioning, mental state, physical health in women with LD indicate the negative impact of the disease on their mental and physical health, which requires additional attention. Conclusion. The most satisfactory in the field of physical and mental functioning are men in comparison group. By gender, higher QOL is higher in men with LD than in women with LD. Mental health indicators on the scale of VT and SF in patients at the average level indicate that the disease does not affect the social life of patients. The lowest indicators on the scales of RE due to emotional state and mental state and the lower indicators on the scales of physical health in women with LD indicate the negative impact of the disease on mental and physical health in women. Therefore, the analysis of not only clinical manifestations, but also taking into account the subjective condition of the patient and changes in mental and physical health will allow to take a comprehensive approach to the treatment of patients with LD and accelerate recovery (especially in women with LD). DOI: 10.5281/zenodo.5499685